Threshold-based cooperative communication of energy harvesting active networked tags. (2017) - Mulatu, Mengistu A.; Chang, Li-Chung; Han, Yunghsiang S.; Mengistu, Fikreselam G.; Tseng, Der-Feng
Using cooperative transmission allows energy-harvesting active networked tags (EnHANTs) to cooperate regarding information transmission and reception, achieving higher throughput compared with non-cooperative counterparts. In this paper, a battery-threshold-based optimal cooperative transmission strategy is proposed for EnHANTs, allowing EnHANT-equipped objects to communicate with the destination (i.e., the reader) either directly or by cooperating with neighbouring objects. A strategy adapted to request states and available energy resources is considered, and an optimal transmission policy for EnHANTs is developed to maximise the long-term average throughput by formulating a Markov decision process (MDP) model. The simulated results indicate that the proposed strategy yields superior performance compared with single-link transmission.